2015
DOI: 10.1111/nph.13313
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of the lignin toolbox of Eucalyptus grandis

Abstract: SummaryLignin, a major component of secondary cell walls, hinders the optimal processing of wood for industrial uses. The recent availability of the Eucalyptus grandis genome sequence allows comprehensive analysis of the genes encoding the 11 protein families specific to the lignin branch of the phenylpropanoid pathway and identification of those mainly involved in xylem developmental lignification.We performed genome-wide identification of putative members of the lignin gene families, followed by comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 91 publications
4
117
0
17
Order By: Relevance
“…The DBH subnetwork contains a considerable number of ligninrelated genes. Most bona fide lignin biosynthesis genes that are highly expressed in developing xylem (8,38) (Dataset S3) were indeed associated with growth (DBH and bark thickness traits). In addition to these lignin-related genes, the DBH network contains several genes involved in hormone signaling (IAA9 and ARF7) and flavonoid biosynthesis (ANS, BAN, and A11).…”
Section: Resultsmentioning
confidence: 99%
“…The DBH subnetwork contains a considerable number of ligninrelated genes. Most bona fide lignin biosynthesis genes that are highly expressed in developing xylem (8,38) (Dataset S3) were indeed associated with growth (DBH and bark thickness traits). In addition to these lignin-related genes, the DBH network contains several genes involved in hormone signaling (IAA9 and ARF7) and flavonoid biosynthesis (ANS, BAN, and A11).…”
Section: Resultsmentioning
confidence: 99%
“…3a). Genes considered bona fide members of lignin biosynthesis 46 were ~4.6-fold enriched for potentially bivalent genes ( P  = 1.93 × 10 −6 ), while genes involved in SCW polysaccharide biosynthesis 20 were not enriched.
Figure 3Relative enrichment of H3K4me3 and H3K27me3 for E. grandis homologs of transcription factors and signal peptides regulating vascular development and flowering in developing secondary xylem tissue. Blue bars, enrichment of H3K4 and H3K27 trimethylation (shown as N-terminal region of histone H3), represented as a signal of zero (no significant enrichment) to four bars (16-fold enrichment).
…”
Section: Resultsmentioning
confidence: 99%
“…The recent completion of whole genome sequencing in Arabidopsis (Raes et al, 2003), Populus trichocarpa (Shi et al, 2010), and Eucalyptus grandis (Carocha et al, 2015) has shown that these model organisms contain COMTs and CCOMTs. A total of 13 COMT-like genes and seven CCOMT genes exist in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%